Socialization of Asset Inventory System Application in MAN 3 Padang Pariaman Goods Management - Kurniawan, Edi; Nazarwin, Nazarwin; Kurniawan, M. (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
The purpose of this service activity is to empower asset inventory management employees at MAN 3 Padang Pariaman through the Socialisation of the Asset Inventory System Application which is expected with this activity the manager can carry out asset and goods inventory management management. The management of the asset inventory system will assist the governance of goods in providing better reports. Improving the inventory management of MAN 3 Padang Pariaman through community service activities is carried out with a team of servants in several stages: (1) the preparation stage, carried out with an initial survey of inventory management then exploration between the two parties. (2) The stage of a memorandum of cooperation agreement, (3) the stage of hearing discussions between the parties (service team) with the Committee and MAN 3 Padang Pariaman regarding the potential and problems that exist in managing the inventory (4) The stage of determining the title as a derivative of the existing service theme as a result of the hearing. The results of community service activities obtained an increase in potential and problems that will be taken into consideration in the sustainability of the target group service programme. One of the most important problems raised is the management of goods with a maintenance asset inventory system.